Japan and its nature (Heibonsha, 1977)
This book introduce eyewitnesses of history, climate of Japan, seas around Japan, mountains of Japan, volcanoes of Japan, plains of Japan, genealogy of Japanese people, made-over nature of Japan, early life of the Japanese islands.